RELEVANSI HUKUM REPRESIF DAN RESPONSIF DALAM MEREKONSTRUKSI NEGARA DEMOKRATIS PANCASILA - Ni Luh Sri Mahendra Dewi (Widyasrama, 2022)
This study raises the theme "Relevance of Repressive and Responsive Law in Reconstructing a Pancasila Democratic State", the focus of the study is on the legal character of each typology, connected with the possibility of a synthesis of legal unification. The character possessed by the legal typology and its application. Second, analyze the material content of legal typology based on legal values that are relevant to the democratic state system and Pancasila ideology as the pillars of the State and Government System based on Democracy. Third, analyzing the direction of legal substance from legal typology and sharpening the possibility of synthesis. The results of the study found that the typologies of repressive law and responsive law have different or contradictory characters. Repressive laws represent power and are bound to the status quo, so that power tends to be effective. Responsive law places law as a means of responding to social will and public aspirations. Responsive law brings a new legal vision with the mission of adopting a new paradigm that prioritizes legal morality and substantial justice.